The umbilical cord mesenchymal stem cell‐derived exosomal lncRNA H19 improves osteochondral activity through miR‐29b‐3p/FoxO3 axis. Issue 1 (13th January 2021) - Yan, Litao; Liu, Gejun; Wu, Xing
Abstract: Background: Our previous study revealed that the exosomal lncRNA H19 derived from umbilical cord mesenchymal stem cells (UMSCs) plays a pivotal role in osteochondral regeneration. In this study, we investigated whether the exosomal lncRNA H19 could act as a competing endogenous RNA (ceRNA) to potentiate osteochondral activity in chondrocytes. Methods: Dual‐luciferase reporter assay, RNA pull‐down, RNA immunoprecipitation (RIP), and fluorescence in situ hybridization (FISH) were carried to verify the interaction between miR‐29b‐3p and both lncRNA H19 and the target mRNA FoxO3. Chondrocytes were treated with UMSC‐derived exosomes, which highly expressing lncRNA H19 expression, followed by apoptosis, migration, senescence, and matrix secretion assessments. An in vivo SD rat cartilage defect model was carried out to explore the role and mechanism of lncRNA H19/miR‐29b‐3p. Results: UMSCs were successfully identified, and exosomes were successfully extracted. Exosomes exhibited the ability to transfer lncRNA H19 to chondrocytes. Mechanistically, exosomal lncRNA H19 potentiated osteochondral activity by acting as a competing endogenous sponge of miR‐29b‐3p, and miR‐29b‐3p directly targeted FoxO3. Intra‐articular injection of exosomes overexpressing lncRNA H19 could promote sustained cartilage repair; however, this effect could be undermined by miR‐29b‐3p agomir. Conclusions: Our study revealed a significant role in the development of strategies against cartilage defects for UMSC‐derived exosomes that overexpress lncRNA H19. Exosomal H19 was found to promote chondrocyte migration, matrix secretion, apoptosis suppression, as well as senescence suppression, both in vitro and in vivo. The specific mechanism lies in the fact that exosomal H19 acts as a ceRNA against miR‐29b‐3p to upregulate FoxO3 in chondrocytes. Abstract : Exosomes derived from UMSCs exhibited the ability to transfer lncRNA H19 to chondrocytes. Exosomal H19 was found to promote chondrocyte migration, matrix secretion, apoptosis suppression, as well as senescence suppression, both in vitro and in vivo. The specific mechanism lies in the fact that exosomal H19 acts as a ceRNA against miR‐29b‐3p to upregulate FoxO3 in chondrocytes.